Stroke Epidemiology in Asia - Narayanaswamy Venketasubramanian (Cerebrovascular Diseases Extra)
Background: Stroke is a major cause of death and disability globally, with different stroke burdens in different regions. This paper reviews the epidemiology of stroke in Asia. Summary: There is a wide range in age- and sex-standardised stroke incidence, highest in China, lowest in Bhutan. Geographically, incidence is highest in East Asia, lowest in South Asia. Stroke mortality is highest in Papua New Guinea, lowest in Singapore. There are variations in mortality within regions – in East Asia, it is higher in Mongolia and North Korea, lowest in Japan; in South Asia, it is higher in Bangladesh and Pakistan, lowest in Sri Lanka; in Southeast Asia, it is higher in Papua New Guinea and Indonesia, lowest in Singapore. Stroke disability-adjusted life years (DALYs) lost is highest in Papua New Guinea, lowest in Singapore. There is intra-regional variation – in East Asia, it is higher in Mongolia and North Korea, lowest in Japan; in South Asia, higher in Bangladesh and Pakistan, lowest in Sri Lanka; in Southeast Asia, it is highest in Papua New Guinea, lowest in Singapore. Among the stroke subtypes, ischaemic stroke (IS) has the highest incidence, intracerebral haemorrhage (ICH) is second, subarachnoid haemorrhage (SAH) is third. IS incidence is highest in China, lowest in Bhutan. The burden due to ICH is highest in Mongolia; ICH incidence is lowest in Sri Lanka, mortality and DALYs are lowest in Japan. SAH has a high incidence in Japan, Singapore, Brunei, and Republic of Korea. In hospital-based registries, the frequency of ICH was highest in Myanmar, low in Mongolia. Among IS, based on the Trial of Org 10,172 in Acute Stroke Treatment classification, large artery atherosclerosis (LAA) is more frequent in some countries (e.g., China, India, Indonesia, Japan, Pakistan, and Republic of Korea), but small artery occlusion (SAO) in most others (Bangladesh, Nepal, Singapore, Sri Lanka, Taiwan, Thailand, and Vietnam); cardioembolism is third. Of the stroke risk factors, hypertension is the most frequent, diabetes mellitus (DM) is usually second, with varying positions for hyperlipidaemia, smoking, and prior stroke or transient ischaemic attacks, obesity, and insufficient physical activity. Key Messages: Asia carries a particularly heavy burden of stroke, higher in some countries. IS is the most common subtype. Among IS, the more common mechanisms are LAA and SAO. Hypertension and DM are the more common risk factors. A greater understanding of stroke epidemiology and risk factors will help in healthcare planning for the prevention and management of stroke. Background: Stroke is a major cause of death and disability globally, with different stroke burdens in different regions. This paper reviews the epidemiology of stroke in Asia. Summary: There is a wide range in age- and sex-standardised stroke incidence, highest in China, lowest in Bhutan. Geographically, incidence is highest in East Asia, lowest in South Asia. Stroke mortality is highest in Papua New Guinea, lowest in Singapore. There are variations in mortality within regions – in East Asia, it is higher in Mongolia and North Korea, lowest in Japan; in South Asia, it is higher in Bangladesh and Pakistan, lowest in Sri Lanka; in Southeast Asia, it is higher in Papua New Guinea and Indonesia, lowest in Singapore. Stroke disability-adjusted life years (DALYs) lost is highest in Papua New Guinea, lowest in Singapore. There is intra-regional variation – in East Asia, it is higher in Mongolia and North Korea, lowest in Japan; in South Asia, higher in Bangladesh and Pakistan, lowest in Sri Lanka; in Southeast Asia, it is highest in Papua New Guinea, lowest in Singapore. Among the stroke subtypes, ischaemic stroke (IS) has the highest incidence, intracerebral haemorrhage (ICH) is second, subarachnoid haemorrhage (SAH) is third. IS incidence is highest in China, lowest in Bhutan. The burden due to ICH is highest in Mongolia; ICH incidence is lowest in Sri Lanka, mortality and DALYs are lowest in Japan. SAH has a high incidence in Japan, Singapore, Brunei, and Republic of Korea. In hospital-based registries, the frequency of ICH was highest in Myanmar, low in Mongolia. Among IS, based on the Trial of Org 10,172 in Acute Stroke Treatment classification, large artery atherosclerosis (LAA) is more frequent in some countries (e.g., China, India, Indonesia, Japan, Pakistan, and Republic of Korea), but small artery occlusion (SAO) in most others (Bangladesh, Nepal, Singapore, Sri Lanka, Taiwan, Thailand, and Vietnam); cardioembolism is third. Of the stroke risk factors, hypertension is the most frequent, diabetes mellitus (DM) is usually second, with varying positions for hyperlipidaemia, smoking, and prior stroke or transient ischaemic attacks, obesity, and insufficient physical activity. Key Messages: Asia carries a particularly heavy burden of stroke, higher in some countries. IS is the most common subtype. Among IS, the more common mechanisms are LAA and SAO. Hypertension and DM are the more common risk factors. A greater understanding of stroke epidemiology and risk factors will help in healthcare planning for the prevention and management of stroke.